Stigma and African genomics research: An exploration of stigma associated with the genetic attribution of rheumatic heart disease - Faure, Marlyn Collin (Department of Medicine, 2019)
There is mixed evidence about how genetic attribution of disease may impact on stigma. One theory, based on essentialism, argues that knowledge of genetic attribution may increase stigma, while attribution theory argues that bio-genetic explanations may result in individuals feeling a decreased sense of personal responsibility about the disease. Most empirical studies shows mixed evidence. These studies however are mostly conducted in Western contexts. This study then is one of the few studies investigating the impact of genetic attribution on stigma in an African context. Specifically, this paper explores the question of genetic attribution with RHD patients in the Western Cape. An important part of this exploration was the use of video content to stimulate discussion in focus groups. Many studies include visual methods and justify the use of visual method based on the assumption that visual methods are more effective at stimulating discussion and generating richer data in qualitative research. In addition to explore the impact of genetic attribution on stigma, this thesis also evaluates the efficacy of visual in qualitative research. Methods: Given that this paper has two components, one investigating the impact of genetic attribution on stigma, and a methodological component, this thesis presents findings of three sub-studies. The primary study (Study 3 in this thesis) related to stigma and genetic attribution, 11 focus group discussions were conducted using vignettes to explore the impact of genetic attribution on stigma with RHD patients. These vignettes were developed into films and used to stimulate discussion in FGDs. Thematic coding analysis was used to analyse data. For the methodological component, one study, presents a systematic review of evidence related to the efficacy of visual methods in qualitative research (Study 1 in this thesis). The final study, is an empirical evaluation of the efficacy of visual methods (Study 2 in this thesis). A before/after study designed was conducted to evaluate the efficacy of visual methods. Six of the FGDs watched the video clips produced from the FGDs, while the other five had the vignettes read to them. Another source of evidence for the evaluation was using the coding density calculated by NVivo 11 software. Results: For the primary study investigating the impact of stigma, the finding show that stigma has a negligible impact of stigma amongst RHD patients in the Western Cape. For the methodological component, the systematic review finds evidence that visual methods are more effective at generating richer data. The evaluation study however finds no difference in results before and after each stimuli, when compared between groups who watched the video or heard the vignettes read. Conclusion: For the primary study investigating the impact of stigma, one of the reasons no evidence was found was because of the low level stigma reported. In instances where stigma is reported, I argue that it is in the context of RHD in this population, the impact of genetic attribution on stigma is displaced given that individuals having multiple explanations models of genetics is just one. Additionally, this population is forced navigate more immediate challenges such as cultural norms, and structural inequality related to the enduring impact of South Africa’s racialised apartheid history. In relation to the methodological component, I argue that results from the systematic review is difficult to generalise given the small number of included studies, and the lack of detail described in the studies, used to evaluate claims that visual methods are more effective. The result of the evaluation finds no difference between the groups which may be there are no differences between these methods, or the questionnaire may have been inappropriate. This study nonetheless is still the first to empirical evaluate such claims.